Analysis Of Financial Performance On Profit In The Food And Beverages Sub Sector Company (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to measure the intended success and assist management in decisions, pluses and minuses and financial considerations. The company certainly expects profit progress in each period, but the difference is that in fact the profit does not match, it actually gets a loss. The achievement of targets is a measure of the success of the company in its operation, as well as the scale or description for future management. Profits are not always profits, but the fulfillment of future targets. With financial reports the best way to get information is through or through ratio analysis in finance. Evaluating financial conditions or performance can use liquidity ratios: Current Ratio (CR), solvency or leverage ratios: Debt To Asset Rati (DAR), activity ratios: Total Asset Turnover (TAT), profitability ratios: Net Profit Margin, Data processing i.e. moving in the food and beverage industry (food and beverages companies. With a period of 5 years (2012-2016), the total is 16 companies, with a sample of 10 companies. Data description of 10 food and beverages companies on the IDX (2012-2016). Simultaneous research results are known the variables CR, DAR, TAT, NPM together have an effect on earnings.